High temperature strength of cast irons for cylinder heads - Guesser W.L.* (2018)
© 2018 Trans Tech Publications, Switzerland.Hot strength and fracture mechanisms in high quality cast irons were studied, comparing the standard gray iron Grade 300, alloyed with Mo, typically used for cylinder heads in high power engines, with other two materials: one gray iron Grade 300, obtained through graphite refinement and one compacted graphite iron, Grade 450. In these last two materials, the strength increase was obtained by changing the graphite structure, not by hardening the matrix. The experimental results with tensile tests carried out up to 500 °C show that the different strengthening mechanisms, use of Mo or modification of the graphite structure, are both efficient for increasing the strength at room temperature as well as at high temperatures. The CGI has a lower strength reduction with temperature than the gray irons, which shows the significant impact of the compacted graphite shape in reducing the notch effect. These results show the enormous potential of CGI in cylinder heads for high-performance engines.